Tinjauan Kritis Polri Sebagai Komponen Pendukung dalam Pertahanan Negara Berdasarkan Putusan Mahkamah Konstitusi Nomor 27/PUU-XIX/2021: A Critical Review of the Indonesian National Police as a Supporting Component in National Defense Based on Constitutional Court Decision No. 27/PUU-XIX/2021 - Raines Wadi; Ruli Agustin; Irwan Triadi (SIYASI: Jurnal Trias Politica, 2024)
The status of the National Police as a Supporting Component as stated in the National Resources Management Law for National Defense and confirmed in Constitutional Court Decision Number 27/PUU-XIX/2021 is problematic. This is because Article 30 paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that the position of the National Police is to carry out efforts to protect and secure the state as the main component. So, the author wants to examine it thoroughly in relation to, firstly, the position of the National Police in protection and security efforts in terms of the 1945 Constitution of the Republic of Indonesia. Second, analyze the existence of the National Police in the Supporting Component of state protection and security efforts. There are two conclusions, namely: First, the position of the National Police in national defense and security efforts based on the initial intention of amending the 1945 Constitution is to synergize with the TNI, especially if a war or armed battle occurs. Second, placing the National Police as a Supporting Component has equalized their rights as citizens who have the principle of the right to refuse military service, while the National Police's protection and security efforts are a constitutional obligation while citizens in military service have a constitutional right.